Nutritional value of high moisture corn silage in the diet of Holstein cows - P. Persichetti Júnior; G.A. Almeida Júnior; C. Costa; P.R.L. Meirelles; J.P.F. Silveira; A. Panichi; M.G.B. Silva; M. A. Factori; F.A. Cavasano; S.A. Mendonça (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2014)
Five Holstein cows were distributed in a 5x5 latin square design to assess the effect of replacement levels of dry ground corn grain (DGCG) by high moisture corn silage (HMCS) on intake, total nutrient digestibility and plasma glucose, according to the following treatments: 1) 100% DGCG; 2) 75% DGCG and 25% HMCS; 3) 50% DGCG and 50% HMCS; 4) 25% DGCG and 75% HMCS; 5) 100% HMCS. The experiment lasted 70 days, divided into five phases of 14 days each. The digestibility was obtained using chromic oxide (Cr2O3) as the indicator. Fecal samples were collected twice daily and blood samples were collected on the last day of each period before the first meal (0h) and 2h, 4h, 6h and 12h after the meal. There was no effect (P>0.05) on the intake of dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF) and starch. The total apparent digestibility of DM, crude protein (CP), NDF and ADF were not affected (P>0.05) by the treatments, as well as the plasma glucose concentration. However, there was a decreased linear effect (P<0.05) for the protein intake and increased linear effect (P<0.05) for starch digestibility, as the level of HMCS was increased in the diets.